2015
DOI: 10.2217/whe.15.40
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Strategies for the Infertile Polycystic Ovary Syndrome Patient

Abstract: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women of reproductive age. Infertility is a prevalent presenting feature of PCOS, and approximately 75% of these women suffer infertility due to anovulation. Lifestyle modification is considered the first-line treatment and is associated with improved endocrine profile. Clomiphene citrate (CC) should be considered as the first line pharmacologic therapy for ovulation induction. In women who are CC resistant, second-line treatment should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 87 publications
0
12
0
2
Order By: Relevance
“…Polycystic ovary syndrome (PCOS), one of the most frequently reported endocrinopathies in women of reproductive age, is characterized by anovulation, hyperandrogenism, and polycystic ovaries syndrome [1,2]. Epidemiologic studies showed that PCOS affected 5–10% reproductive women and it was the leading cause of nearly 75% cases of anovulatory infertility [3]. In addition to the reproductive abnormalities, affected women are more likely to develop various clinical implications, including hyperandrogenism, cardiovascular disease, and endometrial carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS), one of the most frequently reported endocrinopathies in women of reproductive age, is characterized by anovulation, hyperandrogenism, and polycystic ovaries syndrome [1,2]. Epidemiologic studies showed that PCOS affected 5–10% reproductive women and it was the leading cause of nearly 75% cases of anovulatory infertility [3]. In addition to the reproductive abnormalities, affected women are more likely to develop various clinical implications, including hyperandrogenism, cardiovascular disease, and endometrial carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) is a common endocrine disease that affects 6–21% women of reproductive age, approximately 75% of whom experience infertility due to anovulation [1,2]. Its pathological characteristics present diversity and heterogeneity, and include menstrual sparse or amenorrhea, chronic ovulation problem, infertility, increased hair growth, and acne, along with complications such as obesity, hyperandrogenism, hyperinsulinism, and chronic inflammation [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…19 O hormônio folículo estimulante (FSH) sérico nesta síndrome é muito baixo, com isso, gonadotrofinas exógenas podem ser administradas para aumentar seus níveis e estimular o crescimento folicular. 36 Como o FSH estimula o crescimento folicular ovariano, se a liberação de FSH diminui por um longo período, a maturação folicular e, subsequentemente, a ovulação não acontecem e ocorre subfertilidade. A secreção inadequada de gonadotrofinas é o principal atributo da SOP.…”
Section: Gonadotrofinasunclassified